Effect of intranasal mometasone furoate administered in children with coexisting allergic rhinitis and asthma towards asthma attacks and lung function - Ellen P. Gandaputra; Zakiudin Munasir; Bambang Supriyatno; Jose R. L. Batubara (Paediatrica Indonesiana, 2009)
Background Allergic rhinitis and asthma are allergic manifestations in respiratory tract, which related each other. Intranasal corticosteroid is effective in allergic rhinitis and has benefits in decreasing lower airway reactivity.Objectives To evaluate effectiveness of intranasal mometasonefuroate towards asthma in children aged 6-18 years with coexisting allergic rhinitis and asthma.Methods A one group pretest-posttest ("before and after") study was conducted in Cipto Mangunkusumo Hospital from May to December 2008. Subjects were children aged 6-18 years, with moderate-severe intermittent or persistent allergic rhinitis with coexisting frequent episodic asthma or persistent asthma, and visited outpatient clinic of allergy immunology division or respirology division. Subjects were administered intranasal mometasone furoate 100 J-ig daily only for 8 weeks, without long term administration of oral and inhaled corticosteroid. Improvements in allergic rhinitis and asthma were evaluated using questionnaires and lung function tests.Results There were 35 subjects and four of them dropped outduring the study. There was >50% improvement in allergic rhinitis symptoms after 4 weeks of treatment (P<0.001). This improvement was associated with decreasing in frequency of asthma attack >50% after 8 weeks of treatment (P< 0.001). There was an insignificant improvement in FEY 1 (P=0.51). However, the evaluation of sinusitis was not performed in all subjects, thus may influence the results. During study, there were no side effects observed.Conclusions Intranasal mometasone furoate improves allergicrhinitis and decrease >50% of asthma symptoms, however it is not followed with significant improvement in lung function. No side effects are reported during 8 weeks use of intranasal mometasone furoate.